GEOGRAPHIC DISTRIBUTION OF THE SPECIES OF NEODISCOELIUS STANGE (HYMENOPTERA: EUMENIDAE) IN CHILE (Acta Entomológica Chilena, 2022)
This paper offers the distribution of the Neodiscoelius Stange species in Chile. This discussion is basedon studied specimens whose geographic localities are shown.